2005
DOI: 10.1002/pon.886
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for different methods of communicating information regarding adjuvant chemotherapy for breast cancer

Abstract: Many patients play an active role in determining their cancer treatments, and the communication of medical information influences patient decision-making. This study examined participants' preferences between various methods of communicating quantitative risks and benefits of adjuvant chemotherapy. Using clinical vignettes, participants were first asked to decide whether or not to endorse chemotherapy and were subsequently asked about their preferences for the methods used to communicate the risks and benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…In addition to the potential importance of individualized tumor information, others have suggested that the ways recurrence and survival risks are presented may also impact receipt of chemotherapy. [11][12][13] Our findings support the need for further study of how knowledge about one's own disease specifically affects care and outcomes, with inclusion of factors such as information/learning preferences, detailed assessment of health literacy, social supports and whether they were present during discussions, and understanding other potential barriers to care. Certainly, improving knowledge about one's tumor characteristics is a modifiable factor that could be addressed in intervention studies.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In addition to the potential importance of individualized tumor information, others have suggested that the ways recurrence and survival risks are presented may also impact receipt of chemotherapy. [11][12][13] Our findings support the need for further study of how knowledge about one's own disease specifically affects care and outcomes, with inclusion of factors such as information/learning preferences, detailed assessment of health literacy, social supports and whether they were present during discussions, and understanding other potential barriers to care. Certainly, improving knowledge about one's tumor characteristics is a modifiable factor that could be addressed in intervention studies.…”
Section: Discussionsupporting
confidence: 63%
“…[1][2][3][4][5] Studies patients with breast cancer has focused on understanding treatment options, general treatment rationales, and overall treatment benefits or how strategies in communicating recurrence information may affect treatment choices. [5][6][7][8][9][10][11][12][13] One study suggested that women who were under-treated for breast cancer were less likely than treated women to know that breast cancer treatments (ie, hormonal therapy and chemotherapy) improved survival. 8 However, past studies examining cancer knowledge have not focused on how knowing one's own cancer characteristics may affect treatment receipt.…”
Section: Introductionmentioning
confidence: 99%
“…(39,43,44,46,47) The NNT describes the average number of people that should be treated to cure one person. Benefit information was presented, for example, as the absolute survival benefit (ASB) (39,44) or the personal probability of benefit (PPB). (43) These studies have already been discussed in the previous section; we therefore only mention the results related to NNT and benefit information.…”
Section: Number Needed To Treat and Benefit Informationmentioning
confidence: 99%
“…Por outro lado, as razões vulgarmente alegadas pelos partidários de não oferecer informação aos doentes oncológicos centram-se, quase exclusivamente, nas possíveis consequências negativas que poderiam advir da prestação de informação, tais como a apreensão, ira e ansiedade (4,9) outros estudos mostram que dar informações aos doentes tem consequências positivas inclusivamente redutoras e esbatedoras da ansiedade (6,10) , favorecendo uma melhor adaptação psicossocial do doente (10) . Reforça-se, pois, a ideia de que a informação não é um fenómeno de tudo-ou-nada e que, para além disso, o médico não é a única fonte de informação a que o doente recorre, sem que, no entanto, pareça ter perdido o estatuto de fonte privilegiada.…”
Section: A Cronicidade Da Doença Oncológicaunclassified